Canadian Digestive Health Foundation Public Impact Series 5: Pancreatitis in Canada. Incidence, Prevalence, and Direct and Indirect Economic Impact - Christopher W Teshima; Ronald J Bridges; Richard N Fedorak (Canadian Journal of Gastroenterology)
The Canadian Digestive Health Foundation initiated a scientific program to assess the incidence, prevalence, mortality and economic impact of digestive disorders across Canada in 2009. The current article presents the updated findings from the study concerning pancreatitis.